Fuori Uso '94 - Fuoriuso 1994 : Opera Prima. - Bonami, Francesco; Misiano, Victor; Pietrantonio, Giacinto Di (Pescara : Associazione Culturale Arte Nova, 1994)
Acconci, Vito ; Alviani, Getulio ; Armleder, John ; Bijl, Guillaume ; Bill, Max ; Cucchi, Enzo ; Delvoye, Wim ; Garutti, Alberto ; Longo, Robert ; McCarthy, Paul ; Merz, Mario ; Nagasawa, Hidetoshi ; Ontani, Luigi ; Opie, Julian ; Paladino, Mimmo ; Pirri, Alfredo ; Pistoletto, Michelangelo ; Prigov, Dimitrij ; Sherman, Cindy ; Spalletti, Ettore ; Steinbach, Haim ; Zvezdotchotov, Constantin
biografie, bibliografie
Fuori Uso 1994 : Opera Prima, Ex Opificio Gaslini, 22 luglio - 10 agosto 1994
Engels & Italiaans
boek